PENGARUH BEBAN KERJA DAN BUDAYA LAYANAN PADA KOMITMEN BERKARIER SERTA DAMPAKNYA PADA KINERJA KARYAWAN LINI DEPAN HOTEL BERBINTANG LIMA - Goeltom, Vasco Adato H.; Sijabat, Rosdiana; Meilani, Yohana F. C. Palupi; Bernarto, Innocentius (Media Bina Ilmiah, 2024)
Human resources (HR) are very important for operational success because they are responsible for carrying out company activities. Human resource management (HRM) specifically focuses on acquiring the right talent tailored to the company's specific needs. The segmented service industry is currently the main driver of economic growth, and workers play an important role as its main supporters. This research uses quantitative research methods. The source of research data is through distributing questionnaires. The research population is front-line employees of five-star hotels. The number of samples used was 120 respondents. This research uses SEM Partial Least Square (PLS) analysis to analyze variable relationships. The results of the analysis show that service culture and career commitment have a effect on employee performance, except that the influence of workload on career commitment and employee performance are not significant. This highlights the importance of service culture and career commitment in improving performance in the hospitality industry. Overall, this research shows that career commitment and service culture play an important role in improving employee performance. Meanwhile, workload must be managed carefully to ensure that it supports career commitments and employee performance without burdening employees to the point of reducing their performance. Therefore, companies are advised to continue to strengthen their service culture and support employee career commitment to achieve optimal performance.